EVALUATION OF SOME EXTERNAL AND INTERNAL EGG QUALITY TRAITS OF QUAILS REARED IN BASRAH CITY - MUDHAR ABD SALMAN ABU TABEEKH (Basrah Journal of Veterinary Research)
This study was designated to evaluate some external and internal characteristics of quail eggs reared in Basrah city. Ten mature female quails were used in the present study. All birds were reared under similar environmental, managerial and hygienic conditions. To assess the egg quality parameters, a total of 100 eggs were randomly collected for 20 days. The values related to egg weight, shape index, shell weight, shell ratio , shell thickness, egg length, Egg width, Shell index and shell surface area (cm2) are found respectively as 7.041, 79.590, 0.973, 14.193, 0.307, 2.825, 2.245, 13.044 and 8.205. The internal traits as albumen index, albumen height, albumen weight, albumen ratio, albumen width, Albumen length, albumin average, yolk diameter, yolk height, yolk weight, yolk index, yolk ratio and Yolk : Albumen ratio are found respectively as 12.056, 3.204, 2.5, 35.515, 2.308, 3.058, 2.683, 2.195, 3.983, 2.591, 17.601, 36.746 and 1.120.